2012
DOI: 10.4314/wsa.v38i1.1
|View full text |Cite
|
Sign up to set email alerts
|

The chemical oxidation of lignin found in Sappi Saiccor dissolving pulp mill effluent

Abstract: Sappi Saiccor (situated in Durban, South Africa) dissolving pulp mill effluent, produced from an acid bisulphite pulping process, uses acacia and eucalyptus hardwoods to produce a unique and different blend of lignin that has not been previously studied. The chemical oxidation of lignin found in Sappi Saiccor's effluent has been investigated using a number of different chemical oxidising agents, such as nitrobenzene, oxygen with and without the presence of a copper sulphate pentahydrate catalyst, and hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Activation of the biopolymer is carried out to modify functional groups while leaving the aromatic base of the polymer intact [ 17 ]. Originally, lignin was subjected to oxidation to better understand its structure and to identify its bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the biopolymer is carried out to modify functional groups while leaving the aromatic base of the polymer intact [ 17 ]. Originally, lignin was subjected to oxidation to better understand its structure and to identify its bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was supported by study [ 16 ], where nitrobenzene oxidation has been declared as the best oxidation method to produce high yield of aromatic aldehyde from lignin. However, study [ 27 ] reported an opposite finding. Direct oxygen oxidation has been suggested to be capable of producing higher yield of monomeric aromatic compounds than nitrobenzene oxidation when elevated temperature and pressure applied.…”
Section: Resultsmentioning
confidence: 96%
“…According to the results obtained, syringaldehyde was the sole product of OPEFBF lignin nitrobenzene oxidation, followed by hydroxybenzoic acid and vanillin. Under the commonly used temperature setting of nitrobenzene oxidation (~170°C), vanillin and syringaldehyde were always reported to be the main products, to indicate the ratio of guaiacyl and syringyl units in the lignin [ 27 ]. The work in [ 25 , 31 ] reported that OPEFBF lignin contained the highest proportion of noncondensed syringyl units with small amount of noncondensed guaiacyl units and fewer p -hydroxyphenyl units.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moodley et al. used ECO to treat lignin and organic‐extracted mixtures from the Sappi Saiccor pulp mill effluent at a Ni electrode in KOH and NaClO 4 . Electrooxidation of the extracted organic components of the effluent, the concentrated effluent, and lignosulfonate (from Lignotech) all formed syringaldehyde and some vanillin; the product concentrations plateaued in the first 30 min, but declined steadily afterwards possibly due to overoxidation.…”
Section: Electrocatalytic Treatment Of Ligninmentioning
confidence: 99%